Evaluation of antimicrobial, cytotoxicity effects and antioxidant potential of Stemodia verticillata (Mill.) Hassl extract - Alfredi A. Moyo, Sneha R. Bhosale, Kishor S. Jagadhane, Sachin B. Shinde, Vinod B. Shimpale, Prashant V. Anbhule (Journal of Applied Pharmaceutical Science, 2023)
The aim of this study was to evaluate the antimicrobial, cytotoxic, and antioxidant activities of Stemodia verticillata extract. Antimicrobial activity was assessed using agar well diffusion assay and Broth microdilution method, cytotoxicity effects using the 3-(4, 5-dimethylthiazol-2-yl) -2, 5-diphenyltetrazolium bromide assay, the 2,2-diphenylpicrylhydrazyl and ferric reducing antioxidant power assays were used to measure antioxidant. The various bioactive components were identified with the gas chromatography-mass spectrometer (GC-MS) technique. The highest antimicrobial activity was observed against Staphylococcus aureus with a minimum inhibitory concentration (MIC) of 4,000 μg/ml and a minimum bactericidal concentration of 16,000 μg/ml. In comparison, the least activity was observed for Aspergillus niger with a MIC of 16,000 μg/ml and minimum fungicidal concentration of 64,000 μg/ml. The cytotoxicity results revealed the presence of anticancer activity with an IC50 of 79.03 μg/ml against COLO205 colon cancer cell lines. The highest antioxidant activity was exhibited by acetone extract (IC50 = 29.112 μg/ml), followed by 80% ethanolic extract (IC50 = 34.72 μg/ml). The quantitative phytochemical analysis indicated that acetone and 80% ethanolic extracts contained higher amounts of flavonoids and phenolic compounds. Furthermore, five major bioactive compounds were identified by GC-MS. The Findings from the present investigation represent the high potency of S. verticillata extract as a source of more valuable bioactive compounds for developing future phytotherapeutic products.
Keywords: Phytochemicals, antimicrobial, verticillata, cytotoxicity, cancer